Fine-mapping of genetic loci driving spontaneous clearance of hepatitis C virus infection. Issue 1 (December 2017) - Huang, Hailiang; Duggal, Priya; Thio, Chloe; Latanich, Rachel; Goedert, James; Mangia, Alessandra; Cox, Andrea; Kirk, Gregory; Mehta, Shruti; Aneja, Jasneet; Alric, Laurent; Donfield, Sharyne; et al.
Abstract Approximately three quarters of acute hepatitis C (HCV) infections evolve to a chronic state, while one quarter are spontaneously cleared. Genetic predispositions strongly contribute to the development of chronicity. We have conducted a genome-wide association study to identify genomic variants underlying HCV spontaneous clearance using ImmunoChip in European and African ancestries. We confirmed two previously reported significant associations, in theIL28B/IFNL4 and the major histocompatibility complex (MHC) regions, with spontaneous clearance in the European population. We further fine-mapped the association in the MHC to a region of about 50 kilo base pairs, down from 1 mega base pairs in the previous study. Additional analyses suggested that the association in MHC is stronger in samples from North America than those from Europe.